A proposed integrated zakat-crowdfunding model (IZCM) for effective collection and distribution of zakat fund in Malaysia - Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin; Allah Pitchay, Anwar; Khaliq, Ahmad (2019)
This paper has proposed IZCM to assist Zakat institutions for effective collection and distribution of zakat fund in Malaysia. Upon the proposed model, this study examines the behavioural intention of Zakat payers to use IZCM. The primary data are collected from the survey administered to Zakat payers in the Klang Valley (n=250) and the analysis is conducted using Partial Least Squares (SmartPLS). Furthermore, the model has been validated its acceptance in the field by adopting the Technology Acceptance Model (TAM). This study has revealed that both the perceived usefulness and perceived easy to use are found to have a positive impact on the intention of Zakat payers to use IZCM, which later assist Zakat institutions for effective collection and distribution of zakat fund in Malaysia. Furthermore, perceived easy to use has a positive relationship and direct effect with perceived usefulness of Zakat payers to use the IZCM. The findings of this study can be used to develop a specific framework in which to examine other components of using the IZCM’s behavior and to plan appropriate intervention strategies to increase collection and distribution of Zakat fund by Zakat institutions.